Impact of Epstein–Barr virus infection on clinical outcomes and immune profiles in patients with severe fever with thrombocytopenia syndrome - Wang, Tong; Xu, Ling; Li, Hanxin; Zheng, Zhong; Li, Sumeng; Wang, Hua; Liu, Yanan; Zheng, Xin (Frontiers in Immunology, 2026)
BackgroundEpstein–Barr virus (EBV) infection is frequently observed in patients with severe fever with thrombocytopenia syndrome (SFTS), yet its clinical significance remains unclear. This study aimed to characterize the impact of EBV infection on clinical outcomes and the associated immunological and inflammatory profiles in SFTS patients.MethodsA retrospective study was conducted on laboratory-confirmed SFTS patients admitted to Wuhan Union Hospital between January 2021 and June 2025, who were categorized according to plasma EBV DNA status at admission. Propensity score matching (PSM) was applied to address baseline imbalances, and Kaplan–Meier analysis was used to evaluate survival differences. Subgroup analyses using logistic regression were performed to assess the effect of EBV co-infection on mortality. Spearman correlation analyses assessed associations between EBV DNA levels and clinical parameters, and ROC analysis evaluated the predictive performance of immune indicators for EBV infection.ResultsAmong 306 patients with SFTS, 181 (59.2%) were EBV-positive at admission. EBV-positive patients exhibited significantly higher mortality compared to EBV-negative patients (24.3% vs. 8.0%, P < 0.001), although EBV DNA status was not an independent predictor of mortality after multivariable adjustment (OR = 1.31, 95% CI: 0.54–3.17, P = 0.549). The effect of EBV DNA positivity on mortality was more pronounced in elderly patients, those with delayed admission, or comorbidities. Immunological profiling of EBV-positive patients revealed a marked increase in B-cell frequency alongside pronounced reductions in CD3+, CD4+, and CD8+ T cells, with EBV DNA levels strongly correlating with B-cell proportion. Plasma IL-6 and IL-10 levels were markedly increased in EBV-positive group, with EBV DNA positively correlating with IL-10.ConclusionSFTS patients with EBV infection exhibit higher mortality and an immunological profile mirroring that of severe SFTS. Furthermore, EBV DNA may further disrupt B-cell subsets and exacerbate inflammatory dysregulation, thereby intensifying immune dysfunction.